STUDY OF Listeria monocytogenes IN RAW MILK, PASTEURIZED MILK, CHEESE AND DAIRY WASTE - SARKAR, AVIJIT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Listeria monocytogenes has attracted worldwide attention as a food borne pathogen. Present study was conducted with an aim to get the best recovery of Listeria monocytogenes from milk, milk products and dairy waste employing various reported techniques and media. Maximum recovery of L. monocytogenes was obtained by using two stage enrichment techniques with 1:10 dilution with incubation period of 14 days with trypticase soy agar containing yeast extract, potassium thiocyanate and nalidixic acid. The percentage of positive samples for raw milk, pasteurized milk, cheese and dairy waste was 21.33 %, 0%,4%, and 78.66% respectively. Dairy waste gave maximum positive samples of L. monocytogenes .Dairy waste being the most potential source of L. monocytogenes, there is an utmost need to take care to avoid post contamination from dairy environment to prevent spread of the disease like ‘listeriosis ‘through milk and milk products.